Analysis of Complex Pollution and Control of Atmospheric PM2.5 and Ozone in Qinhuangdao. Issue 4 (July 2021) - Wang, Lei; Jin, Tiantian; Suo, Na
Abstract: This paper used the air pollutant monitoring data and meteorological observation data to analayse the compound pollution process of PM2.5 and ozone that appeared in Qinhuangdao City from October 8th-11th, 2020. The causes of pollution were analyse from high-altitude situation, meteorological conditions, pollutant conversion and zone transformation. The results showed that this pollution was affected by the high humidity, static stability and regional transmission. The gaseous pollutants were transformed in the strong oxidizing air which further pushed up the concentration of particles.